Knowledge, practice and attitude toward epilepsy among primary and secondary school teachers in South Gezira locality, Gezira State, Sudan - Haydar E Babikar; Islam M Abbas (Wolters Kluwer Medknow Publications, 2011)
Objective: The attitudes toward school pupils with epilepsy are influenced by the degree of school teachers' knowledge of the disorder. Teachers usually do not receive any formal instructions on epilepsy during their training. This study aims to assess school teachers' knowledge, attitude and practice when dealing with epilepsy in school children. Materials and Methods: This study was part of a series mandated by the Gezira Epilepsy Care Programme (GECP), to obtain baseline data for a community-adapted epilepsy education program. A pretested, semi-structured, 35-items questionnaire was the investigational tool. It was used to evaluate the knowledge of the basic facts about epilepsy among school teachers in this cross-sectional study. The questionnaire allowed teachers to express their opinions by means of free answers. The schools were chosen at random but not in a systematic equiprobability design. Two hundred teachers from public primary (100) and secondary (100) schools in the rural area of south Gezira Locality, Gezira State, Central Sudan, were recruited. Results: In this study, the majority of respondents had never been informed about epilepsy and therefore gave evasive answers to many questions. Few of the respondents considered epilepsy as contagious. None of participants objected to having epileptic children in their classes. Only 47 teachers (47%) in the primary schools had any knowledge of the initial procedures to help a child in seizure, presenting reasonable answers, compared to 64 (64%) teachers in the secondary schools. Recommendations: All school teachers should be given some kind of training in health services. The GECP should involve teachers in its current training programs for caregivers and lay association to help epileptic patients.